Analysis and Experimental Investigation of Oil Jet Flow of Main Reducer Gear based on Flowmaster - Yin Zhimin; Liu Shaojun (Jixie chuandong)
The influence on oil jet flow in nozzle of lubrication system for the main reducer is researched based on the one- dimensional Flowmaster fluid simulation,a more comprehensive and accurate analysis model is put forward. By using the Flowmaster software,the simulation model of oil jet of the main transmission lubrication system is built. Taking the oil pressure 0. 35 MPa and 0. 40 MPa as a single- variable to study the model. Then the simulation and the experimental results are compared and analyzed,the validity and accuracy of the calculation method and model are verified.